OPTIMALISASI DIGITAL MARKETING PASCA PANDEMI COVID-19 PADA PELAKU UMKM KAWASAN WISATA UNIT BANJARAN YOGYAKARTA - Novi Febriyanti; Nuriya Luthfiana; Nurlaili Rohmah; Siti Solehah; Rofiq Burhannudin; Nadya Safia Bilqis; Ardhani Prakoso; Devia Citra Nagari; Muhammad Shalahudin Arrasyid; Aam Indri Febriyanti; Setio Budi (As-Sidanah, 2023)
Micro, Small and Medium Enterprises (MSMEs) in the Banjaran Unit area of Guwosari District, Bantul, Yogyakarta, which are engaged in the culinary business, became collaborators in this activity. MSMEs have problems in the marketing process which is still very basic and conventional, and lack of understanding of financial records. Thus, the author offers guidance on how to manage digital media effectively, as well as how to create financial reports and business accounts on platforms such as Instagram and Linktree and ledgers as a financial recording site. The technique used is a qualitative approach based on outreach, discussion, and providing instructions on how to register an account on digital media and manage the account. The results of this activity indicate that periodic assistance is necessary so that digital marketing tactics can be used effectively and optimally in assisting marketing efforts and boosting sales to MSME companies. Suggestions were made by the activity implementing team so that more MSMEs would receive assistance on the benefits of digital marketing for their businesses. This will be very helpful in encouraging an understanding of digital marketing regarding the steps taken, creating and managing social media applications more optimally for business development.